Ultraviolet/ozone treated polystyrene microcarriers for animal cell culture - Arifin, Mohd Azmir; Mel, Maizirwan; Samsudin, Nurhusna; Hashim, Yumi Zuhanis Has-Yun; Mohd. Salleh, Hamzah; Sopyan, Iis; Nordin, Norshariza (John WIley & Sons Ltd., 2015)
BACKGROUND: Microcarrier based cell culture offers many advantages when compared with conventional cell cultures, and this technology has been widely used in the production of many important biological materials. In this work, microcarriers were produced using materials and methods that are relatively simple and low-cost. RESULTS: Polystyrene (PS) microspheres were prepared by using an emulsion solvent–evaporation method and the effects of process conditions on the size of microspheres were investigated. The mean size of microspheres decreased with increasing agitation speed, concentration of polyvinyl alcohol (PVA) and polymer to solvent ratios but increased with increasing oil to water phase ratios. To enhance its cell attachment abilities, surfaces of PSmicrosphereswere loadedwith oxygen functional groups by using an ultraviolet/ozone (UVO3) system. Analysis by Fourier transform infrared (FTIR), energy dispersive X-ray spectroscopy (EDX), toluidine blue O (TBO) assay and relative contact angle measurements showed increased surface oxygen concentration afte rUVO3 treatment. Results fromspinner flask culture revealed that UVO3 treated PS microspheres support the growth of Vero cells to high cell density. CONCLUSION: UVO3 treatment successfully rendered the hydrophobic surface of PS microspheres hydrophilic. This newly developed microcarrier could serve as a low-cost alternative to commercial microcarriers available in the market today.